Preprocessing of Coefficients for Reusable Continuous Wavelet Transform; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Khamukhin A. A. Aleksandr Anatolievich (Sensors, Measurements and Non-Destructive Control, 2014)
Title screen